2021
DOI: 10.1002/da.23201
|View full text |Cite
|
Sign up to set email alerts
|

The interactions between childhood adversities and recent stress were associated with early‐adulthood depression among Chinese undergraduate students

Abstract: Background It is widely acknowledged that childhood adversities (CAs) and recent stress are potential risk factors for adult depression. However, the mechanism(s) by which interactions of CAs with recent stress affect adult depression remain unclear. Aims To investigate the predictive association of the interaction among CAs and recent stress with early‐adult depression. Method We conducted an annual survey of all freshmen for the period of 2016‐2018 in a Chinese comprehensive university, with a sample size of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 59 publications
(84 reference statements)
0
5
0
Order By: Relevance
“…For adolescents, life events stress generally includes failing exams, transferring or dropping out of school, fighting with classmates, conflicts with family, being discriminated against, having a bad or broken relationship, being punished for truancy, and so on (X. Liu et al, 1997; Xin & Yao, 2015). Life events stress is found to moderate the association between childhood trauma and a wide range of negative development outcomes, such that individuals exposed to greater childhood trauma and recent stress are at greater risk of executive function deficits (Ayesa‐Arriola et al, 2020), and internalizing and externalizing behavior problems such as emotional problems (e.g., anxiety, depression) and suicide ideation and suicide behavior (Duprey et al, 2021; Farmer & Kashdan, 2015; Li et al, 2021; McLaughlin et al, 2010; Miller et al, 2017; Nederhof et al, 2014; Oldehinkel et al, 2014; Rousson et al, 2020; Wade et al, 2019). In addition, life events stress is also found to interact with executive function to affect internalizing and externalizing behavior problems, such that adolescents and young adults who have poor executive function are more likely to suffer anxiety, depression, and aggression when they exposed to recent stress (Clarke, 2011; De Lissnyder et al, 2012; Shields et al, 2017; Sprague et al, 2011; Y. Zhou et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…For adolescents, life events stress generally includes failing exams, transferring or dropping out of school, fighting with classmates, conflicts with family, being discriminated against, having a bad or broken relationship, being punished for truancy, and so on (X. Liu et al, 1997; Xin & Yao, 2015). Life events stress is found to moderate the association between childhood trauma and a wide range of negative development outcomes, such that individuals exposed to greater childhood trauma and recent stress are at greater risk of executive function deficits (Ayesa‐Arriola et al, 2020), and internalizing and externalizing behavior problems such as emotional problems (e.g., anxiety, depression) and suicide ideation and suicide behavior (Duprey et al, 2021; Farmer & Kashdan, 2015; Li et al, 2021; McLaughlin et al, 2010; Miller et al, 2017; Nederhof et al, 2014; Oldehinkel et al, 2014; Rousson et al, 2020; Wade et al, 2019). In addition, life events stress is also found to interact with executive function to affect internalizing and externalizing behavior problems, such that adolescents and young adults who have poor executive function are more likely to suffer anxiety, depression, and aggression when they exposed to recent stress (Clarke, 2011; De Lissnyder et al, 2012; Shields et al, 2017; Sprague et al, 2011; Y. Zhou et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…According to a prior study (Li et al, 2021), Chinese undergraduate students frequently reported having experienced childhood hardships, which raised their risk of developing depression in their early adult years. The study's results also supported the comorbidity between MDD and a history of exposure to parental conflict.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have pointed out that individuals who 1382 experienced childhood stress were associated with mental disorders in adulthood. [13][14][15][16][17][18][19] Therefore, the role of childhood stress in occupational stress response should be considered in any occupational stress assessment or prevention. This study provides a new tool (see Appendix 1) for occupational stress measurement in medical staff.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated that individuals who experienced stress or trauma in childhood are prone to mental disorders in adulthood. [13][14][15][16][17][18][19] Therefore, the effect of childhood stress on occupational stress response was considered during the assessments.…”
Section: Methodsmentioning
confidence: 99%